Чёрные реки сердца: роман / Дин Кунц - Кунц Дин Рэй (Серия эксклюзивная "VIP", 1995)
Экземпляры: ф. 2 (20120123) / Инвентарный номер: 97828 / Цена: 35.00 / Авт.знак: К 91 / ГРНТИ: 17.82 / ББК: 84(7Сое)